UTILIZATION OF CORPORATE SOCIAL RESPONSIBILITY FUNDS IN DESIGNATED OPEN GREEN SPACE DEVELOPMENT - Yosi Andri, Gusti; Dikrurrahman, Diky; Sutrisno, Endang (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
One of the open green spaces functions as a water absorption medium, but it still needs to be fully implemented by the Cirebon Municipality Government. From the data obtained, only around 11% of public open green space has been fulfilled out of 20%, according to Cirebon's neighborhood units. The problems faced include limited land ownership and difficulties in the land acquisition process. This research aims to analyze and find solutions for creating public open green space in Cirebon. Applied research methods are used to find solutions to problems that occur in the community regarding the provision of public open green space. The results of the research show that the use of Social and Environmental Responsibility funds (Corporate Social Responsibility) can be one solution to overcome the problem of public open space in Cirebon, considering that Cirebon is a hub for trade and service routes where apart from residential areas there are also many shops, hotels, offices, Government and private sectors have offices in Cirebon. Social and Environmental Responsibility is integral to sustainable development goals involving stakeholders (Government and society). Procurement of land in areas in each village/district and settlements to create public open green space by utilizing CSR funds until Cirebon is achieved as a Green City. Also, the concept of conservation in open green space areas can be created to support the community's economy. This anticipates the emergence of impromptu micro businesses whose impact will disrupt order and cleanliness around public open green space, which can eliminate the main objective of developing open green space itself.